2007
DOI: 10.1016/j.jpsychires.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A review of diffusion tensor imaging studies in schizophrenia

Abstract: Both post-mortem and neuroimaging studies have contributed significantly to what we know about the brain and schizophrenia. MRI studies of volumetric reduction in several brain regions in schizophrenia have confirmed early speculations that the brain is disordered in schizophrenia. There is also a growing body of evidence suggesting that a disturbance in connectivity between different brain regions, rather than abnormalities within the separate regions themselves, are responsible for the clinical symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
532
2
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 689 publications
(574 citation statements)
references
References 74 publications
27
532
2
8
Order By: Relevance
“…However, the association between aberrant pruning and schizophrenic symptomatology remains difficult to prove in vivo, e.g. using EEG (Micheloyannis et al, 2006), fMRI (Liu et al, 2008), or DTI (Kubicki et al, 2007). In this study, we observed that adult patients with 22q11DS and without schizophrenia demonstrate preserved thickness as compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 60%
“…However, the association between aberrant pruning and schizophrenic symptomatology remains difficult to prove in vivo, e.g. using EEG (Micheloyannis et al, 2006), fMRI (Liu et al, 2008), or DTI (Kubicki et al, 2007). In this study, we observed that adult patients with 22q11DS and without schizophrenia demonstrate preserved thickness as compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 60%
“…However, with newer, faster MR systems, where it is not too costly to use higher directional resolution, one should certainly consider doing so. Additionally, we note that tractography stopping criteria of 20° of curvature change within 1 mm, are quite common in the literature, and have been introduced in order to deal with potential artifacts in the data that could influence the tractography output (see review in Kubicki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[76][77][78][79] These oligodendrocyte abnormalities may in turn contribute to the loss of coherence of axon tracts, and reduced connectivity, in schizophrenia. 80,81 Alterations in NRG1-ERBB4 and/or PTPRZ1 signaling may cause these oligodendrocyte abnormalities, in addition to potential neuronal effects.…”
Section: Discussionmentioning
confidence: 99%